The SmAP1/2 proteins of the crenarchaeon Sulfolobus solfataricus interact with the exosome and stimulate A-rich tailing of transcripts. Issue 13 (18th May 2017) - Märtens, Birgit; Hou, Linlin; Amman, Fabian; Wolfinger, Michael T.; Evguenieva-Hackenberg, Elena; Bläsi, Udo
Abstract: The conserved Sm and Sm-like proteins are involved in different aspects of RNA metabolism. Here, we explored the interactome of SmAP1 and SmAP2 of the crenarchaeon Sulfolobus solfataricus (Sso) to shed light on their physiological function(s). Both, SmAP1 and SmAP2 co-purified with several proteins involved in RNA-processing/modification, translation and protein turnover as well as with components of the exosome involved in 3΄ to 5΄ degradation of RNA. In follow-up studies a direct interaction with the poly(A) binding and accessory exosomal subunit DnaG was demonstrated. Moreover, elevated levels of both SmAPs resulted in increased abundance of the soluble exosome fraction, suggesting that they affect the subcellular localization of the exosome in the cell. The increased solubility of the exosome was accompanied by augmented levels of RNAs with A-rich tails that were further characterized using RNASeq . Hence, the observation that the Sso SmAPs impact on the activity of the exosome revealed a hitherto unrecognized function of SmAPs in archaea.